2013
DOI: 10.1248/bpb.b12-00315
|View full text |Cite
|
Sign up to set email alerts
|

Survey on the Attitudes of Pharmacy Students in Japan toward Doping and Supplement Intake

Abstract: Doping is one of the most serious problems for athletes, and it is important that pharmacists have more interaction with athletes to ensure safer drug usage. Education is one of the most important roles of sports pharmacists, who are specialists regarding drug usage for athletes. We investigated pharmacy students' interests and comprehension regarding drug usage, doping and supplement intake by using the form of a questionnaire, since it is important to know how they understand these subjects as part of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 6 publications
4
17
1
1
Order By: Relevance
“…In alignment with previous studies, 2,3 our study demonstrated that pharmacy students support sports pharmacy being incorporated into the curriculum. Settings proposed for sports pharmacy content include the classroom, postgraduate training, and experiential programs.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…In alignment with previous studies, 2,3 our study demonstrated that pharmacy students support sports pharmacy being incorporated into the curriculum. Settings proposed for sports pharmacy content include the classroom, postgraduate training, and experiential programs.…”
supporting
confidence: 89%
“…One point was awarded for each correct response in the substance list shown in Table 2, giving rise to a maximum knowledge score of 8. The overall knowledge score of participants showed a mean (SD) of 4.1 (1.7) and median (inter-quartile range) of 4 (2). Inferential analysis of socio-demographic factors that might affect participants' knowledge regarding anti-doping was conducted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear if this trend represents a lack of available courses or workshops on the topic, or if the practitioners themselves don't perceive the issue to be as important as other clinical education topics. However, a study conducted in Japan that investigated pharmacy students' interests and comprehension regarding drug usage, doping and supplement intake also indicated that the students did not have opportunities to learn about doping and supplement intake (with only 16% of the students attending lectures by specialists on doping) and that their basic knowledge regarding doping was limited [7]. In our study, >92% of all respondents (i.e.…”
Section: Discussioncontrasting
confidence: 59%
“…Many reports showed an increase in the prevalence of prescription drug abuse [14][15][16]. Therefore, there is always a need for pharmacists to have the confidence and ability to offer psychosocial and medication recommendations to patients and other health care professionals about addictionrelated issues and their associated hazards, particularly because of the difficulties involved in recognizing addiction [14][15][16].…”
Section: Introductionmentioning
confidence: 99%